Ischemic complications after percutaneous radiofrequency ablation of liver tumors: Liver volume loss and recovery. Issue 4 (6th February 2019) - Wake, Taijiro; Tateishi, Ryosuke; Nakagomi, Ryo; Fujiwara, Naoto; Kinoshita, Mizuki Nishibatake; Nakatsuka, Takuma; Sato, Masaya; Minami, Tatsuya; Uchino, Koji; Enooku, Kenichiro; Nakagawa, Hayato; Asaoka, Yoshinari; et al.
Abstract : Aim: The liver regrows after acute liver injury and liver resection. However, it is not clear whether the liver regenerates in advanced cirrhosis. This study aimed to evaluate the clinical course of, and liver volume change after, ischemic liver complications caused by radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC). Methods: We enrolled 35 patients with ischemic complications after RFA. Ischemic complications were defined as rapid elevation of aspartate aminotransferase (AST) to over 500 U/L, with typical radiological findings. Patient characteristics and the ischemic liver volume were investigated. Long‐term liver volume changes at 3–8 months after ischemic complications were also assessed in 32 patients. We also assessed the overall survival rate after ischemic complications. Results: The median value of peak AST was 798 U/L (range, 531–4096 U/L). The median ischemic liver volume relative to the functional liver volume before RFA was 13% (range, 3.1–46.5%). There was a strong correlation between the peak AST value and the ischemic liver volume (r = 0.84, P < 0.001). The liver volume recovered to some extent in 18 of 32 (56%) patients after ischemic complications. The survival rate after ischemic complications was 45.7% at 5 years and correlated with the functional liver volume after ischemic complications ( P = 0.02). Conclusions: Ischemic complications after RFA can lead to massive liver parenchymal loss. Although the liver volume recovered to some extent in the majority of our patients, ischemic liver complications after RFA should be avoided to improve the overall survival rate.